2020
DOI: 10.22359/cswhi_11_3_03
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Activity on the Quality of Life of Seniors Living in Retirement Homes

Abstract: Objective: The aim of this research to find out whether physical activity (PA) affects the quality of life (QoL) of seniors living in retirement homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Physical exercises lead to the flexibility of muscles, tendons, ligaments, have a beneficial effect on body posture, improve the psychophysical state of the body [2,5,6]. Kendrova et al [9] showed a beneficial effect of physical activity on the quality of life of a retirement home residents in Sabinov (Slovakia), examined with the WHOQOLBREF questionnaire. Kurowska's research [10] showed that elderly women preferred meetings with friends, activities improving physical fitness, watching TV and learning new things in their free time, while men preferred acquiring new skills, improving physical fitness and watching TV.…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercises lead to the flexibility of muscles, tendons, ligaments, have a beneficial effect on body posture, improve the psychophysical state of the body [2,5,6]. Kendrova et al [9] showed a beneficial effect of physical activity on the quality of life of a retirement home residents in Sabinov (Slovakia), examined with the WHOQOLBREF questionnaire. Kurowska's research [10] showed that elderly women preferred meetings with friends, activities improving physical fitness, watching TV and learning new things in their free time, while men preferred acquiring new skills, improving physical fitness and watching TV.…”
Section: Introductionmentioning
confidence: 99%
“…It is especially important for seniors, because the aging of the human body causes changes in the structure and functions of organs, reduces psychophysical efficiency [2][3][4][5]. Data from the literature indicate that physical activity has a significant impact on increasing independence and selfreliance, and thus improves the quality of life of the elderly [6,7]. In line with World Health Organization recommendations [8], older adults should do at least 150-300 minutes of moderate intensity aerobic physical activity; or at least 75-150 minutes of vigorousintensity aerobic physical activity; or an equivalent combination of moderate and vigorousintensity activity throughout the week, for substantial health benefits.…”
Section: Introductionmentioning
confidence: 99%